2008
DOI: 10.1007/s00198-008-0743-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of incident fractures on health-related quality of life: 5 years of data from the Canadian Multicentre Osteoporosis Study

Abstract: BackgroundVertebral fractures in patients with cystic fibrosis (CF) may contribute to an accelerated decline in lung function and can be a contraindication to lung transplantation. In this study, we examined longitudinal change in bone mineral density (BMD) and the prevalence of vertebral fractures in adult CF patients, without lung-transplant, attending a Canadian specialty clinic.MethodsRetrospective chart review of all patients attending an Adult Cystic Fibrosis Clinic at Hamilton Health Sciences in Hamilto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(108 citation statements)
references
References 61 publications
5
97
2
4
Order By: Relevance
“…After a hip fracture, mobility, ambulation, and self-care are significantly affected. 4,[18][19][20][21] This reduction in quality of life has been shown to persist for several years. 20 Spine fractures result in severe pain and reductions in general health and vitality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After a hip fracture, mobility, ambulation, and self-care are significantly affected. 4,[18][19][20][21] This reduction in quality of life has been shown to persist for several years. 20 Spine fractures result in severe pain and reductions in general health and vitality.…”
Section: Discussionmentioning
confidence: 99%
“…4,[18][19][20][21] This reduction in quality of life has been shown to persist for several years. 20 Spine fractures result in severe pain and reductions in general health and vitality. In contrast to hip fractures, the negative impact of spine fractures occurs primarily in those who experienced fracture more recently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fact that there is no accurate test to determine Ca 2þ deficiency, it is considered that women must meet the recommended Ca 2þ intake levels (52) . Although a low-Ca 2þ diet has been considered as a risk factor for developing osteoporosis, a recent article reviewing several databases for low BMD or for bone loss in healthy men aged 50 years or older has found that dietary Ca 2þ is a weak risk factor for low BMD (53) . The interaction of dietary Ca 2þ content and physical activity seems to be very important to determine adequate BMD.…”
Section: Low-ca 21 Diets and Bonementioning
confidence: 99%
“…The consequences of fractures, particularly hip and spine, can be devastating and may be most severe in the elderly [4]. Fractures lead to substantial pain, reduced quality of life, dependence in self-care and mobility, institutionalization, and mortality [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%